Mary Shelley's Frankenstein, Disability, and the Injustice of Misrecognition - Knight, Amber (Disability Studies Quarterly, 2020)
This article makes the case that the normative aspirations of recognition politics are worth pursuing as a dimension of disability politics— although the tactics need to be revised— through an interpretation of Mary Shelley's Frankenstein. Specifically, I read Frankenstein's Creature as a visibly disabled subject, as someone who is misrecognized and mistreated due to his body's physical features, in order to analyze the tragedy of the novel: how the not-so-monstrous Creature can never see himself as anything other than a monster since he is never afforded the positive recognition he desires. The article concludes by considering how the tragedy could have been avoided in an attempt to envision a better path toward social justice for people with disabilities and other victims of identity-based subordination. More broadly, this article attempts to bring Mary Shelley into the political theory canon, casting her as a progressive social critic who believed that misrecognition creates monsters out of those who are negatively labelled as such.